Perception of family health strategy users on emergency service - Leonidas Reis Moura; Elyrouse de Sousa Brito Rocha; Maria Eliete Batista Moura; Fabrício Ibiapina Tapety; Gerardo Vasconcelos Mesquita (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: To analyze the users' perception of the Family Health Strategy on the urgent and emergency care provided in primary healthcare. Methods: A qualitative descriptive exploratory study with 30 users. A semi-structured interview was used as a data collection technique. The data were processed using the software Alceste 4.8. Results: Four classes were constructed: User satisfaction with the urgent and emergency care; Unit structure for urgent / emergency care; Justifications for seeking urgent and emergency care; Understanding of the meanings of urgent and emergency. Conclusion: The study showed that users are satisfied with the care received in the units although they present ambiguity when it comes to their physical structure. The respondents also failed to conceptualize urgent and emergency, and showed that the cause that led them to seek the healthcare units were changes in blood pressure, diabetes and trauma.